If f(x)=e^x-1 +5 and g(x) is a transformation or, the same thing just moved, and its y-intercept is -3 then its equation would be:
D) g(x)=e^x-1 -3
Step-by-step explanation:
25 is the answer . hope it helps
(f-g)(x) = f(x) - g(x)
= (x^3 -2x+6) - (2x^3+3x^2-4x+2)
= x^3 -2x +6 -2x^3 -3x^2 +4x -2 . . . . distribute the negative sign
= (1-2)x^3 -3x^2 +(-2+4)x +(6-2) . . . . . combine like terms
(f-g)(x) = -x^3 -3x^2 +2x +4
D, one number is positive and the other is negative. The only way it could equal 0 is to cross the other out. An example is, -5+5=0